THE FUNCTIONAL ABILITIES AND THEIR DIFFERENCES BETWEEN THE VOLLEYBALL TEAMS FROM THE REPUBLIC OF MACEDONIA AND THE REPUBLIC OF KOSOVO IN PRE- COMPETETION PERIOD - Nazmie Ibrahimi; Abedin Ibrahimi; Zorica Stankovska; Vesna Bratovčić; Zarko Kostovski (Sport Scientific And Practical Aspects, 2025)
The study was conducted on a stratified sample of two subsamples of subjects to determine the level and differences in heart rate, blood lactate, anaerobic threshold, VO2max. in volleyball players in the pre-competition period. The sample of respondents was taken from the population of volleyball players, a total of 43, members of the representative teams of the volleyball league of the Republic of Macedonia and the Republic of Kosovo. The study used a total of 6 variables to assess the functional abilities of female volleyball players. Using multivariate analysis of variance (MANOVA), statistically significant differences between groups were found at the level of p = 0.00. Testing differences between arithmetic means for each variable with univariate analysis of variance (ANOVA), where no statistically significantdifferences were found between the two teams.